INKABER AS AN INNOVATION LEARNING MODEL TO IMPROVE READING AND WRITING SKILLS FOR BEGINNERS - Anita Alfajriya; Ahmad Taufiq (Tadibia Islamika, 2021)
This study aims to determine students’ reading and writing skills through the inkaber model in MI Islamiyah Reban, how the planning of the Inkaber model in fostering initial reading and writing skills, the implementation of the Inkaber model in fostering initial reading and writing skills and the advantages and disadvantages of using the Inkaber model in learning MI Islamiyah Reban. This research is a type of field research with a qualitative approach to education and data collection by conducting observations, interviews, and documentation to complement the data. The data analysis used is descriptive qualitative by providing an explanation of the data collected. Data checking is done by triangulating or comparing data from various sources and drawing conclusions. From the research results, it can be concluded that the Inkaber model is a learning innovation to foster students’ initial reading and writing skills MI Islamiyah Reban which is implemented through presenting familiar pictures by finding vocabulary that matches the picture and writing them down then making these simple sentences can have a good influence on students’ reading and writing skills. This is shown in the activeness of students when participating in learning and enthusiasm in learning to read and write. Students are also more interested in the learning process in class because they learn through familiar pictures.